An angiographic atlas of intracranial arterial diameters associated with cerebral aneurysms. (13th August 2013) - Mocco, J; Huston, John; Fargen, Kyle M; Torner, James; Brown, Robert D
Abstract : Introduction: The successful treatment of intracranial aneurysms is dependent on a full understanding of the anatomic relationship of a given aneurysm to its parent artery(s) and nearby branches. Furthermore, new endovascular technologies are often limited by size constraints. Currently, there is no complete atlas describing diameters for each major intracranial arterial segment. We sought to obtain these data by performing a systematic analysis of selected cerebral angiography images from the International Study of Unruptured Intracranial Aneurysms (ISUIA). Methods: Four hundred and forty-five patients with unruptured intracranial aneurysms from the ISUIA database were reviewed. Using previously described techniques, artery diameters were measured for all arteries involved in the aneurysm neck for each patient. Results: Measurements were obtained from 695 different aneurysm-associated arterial segments among 445 patient angiograms (mean 1.6 measurements per aneurysm). Artery diameters, mean, median, SEM and IQRs based upon the different arterial segments are presented. Conclusions: This angiographic almanac of aneurysm-associated intracranial arterial diameters may be of benefit in establishing standard norms through which devices, protocols and research aims may be developed.